2004
DOI: 10.1177/026119290403201s29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditioning on the Increase of Heart Rate and Body Temperature Provoked by Handling in the Mouse

Abstract: To assess the effect of procedures on animal welfare, various physiological parameters, such as body weight, hormone levels in plasma and/or urine, heart rate (HR), blood pressure and body temperature (BT), can be used. When measuring physiological parameters with techniques involving restraint of the animals, the results must be interpreted with caution, since restraint itself may have an effect on those parameters. Radio-telemetry, using an implantable transmitter, provides a way to obtain more accurate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…While there is evidence that this might be the case to some degree and in some circumstances, there is also substantial evidence to the contrary -i.e. that stress may become worse due to repeat exposures; that habituation/desensitisation applies to only some types of stressor and not others; that while some indicators of stress may decrease, others do not, confounding the issue; and so on (see various examples [7][8][9][10][11][12][13] ).…”
Section: Jarrod Baileymentioning
confidence: 99%
“…While there is evidence that this might be the case to some degree and in some circumstances, there is also substantial evidence to the contrary -i.e. that stress may become worse due to repeat exposures; that habituation/desensitisation applies to only some types of stressor and not others; that while some indicators of stress may decrease, others do not, confounding the issue; and so on (see various examples [7][8][9][10][11][12][13] ).…”
Section: Jarrod Baileymentioning
confidence: 99%
“…Syversen et al (2008) for example found fluctuations in temperature of 11 °C during air transfer in more than 60% of shipments [ 16 ]. It is known that stress-induced-hyperthermia and ambient temperature (T a ) affect body temperature (T b ) [ 17 , 18 , 19 , 20 , 21 , 22 ]. Results of studies measuring T b before and after transfer, however, are inconsistent: Capdevilla et al (2007) [ 11 ] found no effect of transfer of rats on T b , while Dallman et al (2006) [ 23 ] observed an increase in T b of rats when moving a cage within the same room or to another room, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Although handling is accepted as stressful to mice, there is no total agreement as to whether mice can be habituated to handling with a meaningful reduction in the stress response. 11,14 Handling is made up of many variables including the specific technique of how the mouse is captured and other factors such as the handler and the environment. Moreover, differences in sensory adaptations between humans and mice render the scientist unaware of many environmental variables, such as auditory and olfactory stimuli, that can affect experimental conditions.…”
mentioning
confidence: 99%